Evaluation of a pilot family planning educational seminar and subsequent attitudes towards family planning among Muslim communities in Tanzania - Alexandra A. Cordeiro; Hajirah Gumanneh; Aneth Nzali; Valencia J. Lambert; Amina Yussuph; Albert Kihunrwa; Yassin Mchondo; Ramadhan Mtita; Hidaya Yahaya; Samuel E. Kalluvya; Joyce Wamoyi; Mehrunisha Suleman; et al. (PLoS ONE, 2025)
Evidence has demonstrated that uncertainty about compatibility with religious beliefs and limited health knowledge hinder uptake of family planning (FP), even among women who would like to prevent or delay childbearing. Empowering women and men to choose the number and timing of children is a global goal and enhances both maternal and child health. Building on data demonstrating the effectiveness of religious leaders in Tanzania to provide public health information in communities, the aim of this study was to understand whether and how an educational seminar about FP that was provided to Tanzanian Muslim religious leaders could be an effective means by which education about FP could reach members of their communities. This study employed a mixed-methods approach to pilot-test a one-day educational seminar about social, medical, and theological aspects of FP. The seminar was provided to Muslim religious leaders from two mosques in northwest Tanzania in April 2022. Six weeks after the seminar, the same religious leaders were invited to evaluate the seminar both by a quantitative survey assessing acceptability, appropriateness, and feasibility, and in in-depth interviews. Interviews explored participants’ knowledge and perceptions of FP, views of its permissibility in Islam, and actions that they had taken since attending the seminar. Demographic and survey data was analyzed using R software. Thematic analysis using de-identified transcripts was performed using NVivo (Version 12). In June 2022, 48 Muslim religious leaders (26 women; 22 men) completed the quantitative survey and in-depth interviews. Participants rated the seminar as highly acceptable, appropriate, and feasible, with mean scores above 4.5 out of 5 for every statement. Participants viewed the seminar as enlightening and expressed that it improved their knowledge about FP and enabled them to consider FP from both medical and Islamic faith-based viewpoints. Others described having taught their communities about FP and described the positive impact the seminar had for enhancing couple communication and enabling FP uptake for those desiring to use it. Almost all participants recommended that the seminars return to their community more frequently and indicated the importance of allowing discussion time for men and women separately during part of the seminar. Muslim religious leaders reported feeling equipped by an educational seminar to teach about FP to their communities. These data highlight the high potential of trusted religious leaders to build knowledge about FP, which could address women’s current unsatisfied demand for FP and promote maternal and child health in Muslim communities in Tanzania.